A Systematic Review to Compare Chemical Hazard Predictions of the Zebrafish Embryotoxicity Test With Mammalian Prenatal Developmental Toxicity. (9th June 2021) - Hoffmann, Sebastian; Marigliani, Bianca; Akgün-Ölmez, Sevcan Gül; Ireland, Danielle; Cruz, Rebecca; Busquet, Francois; Flick, Burkhard; Lalu, Manoj; Ghandakly, Elizabeth C; de Vries, Rob B M; Witters, Hilda; Wright, Robert A; et al.
Abstract: Originally developed to inform the acute toxicity of chemicals on fish, the zebrafish embryotoxicity test (ZET) has also been proposed for assessing the prenatal developmental toxicity of chemicals, potentially replacing mammalian studies. Although extensively evaluated in primary studies, a comprehensive review summarizing the available evidence for the ZET's capacity is lacking. Therefore, we conducted a systematic review of how well the presence or absence of exposure-related findings in the ZET predicts prenatal development toxicity in studies with rats and rabbits. A two-tiered systematic review of the developmental toxicity literature was performed, a review of the ZET literature was followed by one of the mammalian literature. Data were extracted using DistillerSR, and study validity was assessed with an amended SYRCLE's risk-of-bias tool. Extracted data were analyzed for each species and substance, which provided the basis for comparing the 2 test methods. Although limited by the number of 24 included chemicals, our results suggest that the ZET has potential to identify chemicals that are mammalian prenatal developmental toxicants, with a tendency for overprediction. Furthermore, our analysis confirmed the need for further standardization of the ZET. In addition, we identified contextual and methodological challenges in the application of systematic review approaches to toxicological questions. One key to overcoming these challenges is a transition to more comprehensive and transparent planning, conduct and reporting of toxicological studies. The first step toward bringing about this change is to create broad awareness in the toxicological community of the need for and benefits of more evidence-based approaches.